Children’s Ministry in April - Cowie, George (The expository times, 2011)
The article looks at different sermons for children's ministry. One address was based from the Old Testament, 1 Samuel 16:1-13 in which the story involved David being annointed as king. A Gospel reading from John 11:1-45 related a story in which Jesus Christ wept when he learned that his friend Lazarus had died. Another sermon from John 20:1-18 focused on the issue of resurrection.